The new values unfolding : worktext in values education - Galicia, Jane S. (Sampaloc, Manila : Rex Book Store, Inc., 2018)
"Children are brought to the world and entrusted by God to the care of their parents for them to praise and honor their Creator. They are beautiful and precious gifts. At an early age, they should be molded and nurtured. Nurturing should be continuous. They need that much cherished relationship with their parents, their teachers in school, their community, and their country in general. As children begin to mature, they should move forward to a bright future. This textbook is the answer to the needs of the pupils in elementary to become values motivated, both inside and outside of school. It aims to make them creative, responsive, respectful, compassionate, and sensitive to their needs and the needs of others, including the environment. It is important that the pupil develops the knowledge, feelings, and the motivation to make him or her a better person, and eventually live a motivated life. If a child has these, he or she can live and work well, develop his or her potentials, and make the right decisions."
Includes glossary and bibliography.
English text.
Keywords: Values education -- Study and teaching